Large mass hierarchies from strongly-coupled dynamics - Maurizio Piai (Pos(Lattice2016)232, 2017)
Motivated by the absence of signals of new physics at the LHC, which seems to imply the presenceof large mass hierarchies, we investigate the theoretical possibility that these could arise dynamicallyin new strongly-coupled gauge theories extending the standard model of particle physics.To this purpose, we study lattice data on non-Abelian gauge theories in the (near-)conformalregime—specifically, SU(2) with Nf = 1 and 2 dynamical fermion flavours in the adjoint representation.We focus our attention on the ratio R between the masses of the lightest spin-2 andspin-0 resonances, and draw comparisons with a simple toy model in the context of gauge/gravitydualities. For models in which large anomalous dimensions arise dynamically, we show indicationsthat this mass ratio can be large, with R > 5. Moreover, our results suggest that R mightbe related to universal properties of the IR fixed point. Our findings provide an interesting steptowards understanding large mass ratios in the non-perturbative regime of quantum field theorieswith (near) IR conformal behaviour.